Meningkatkan Hasil Belajar PAK melalui PBL Materi Kebebasan Anak-Anak Allah Fase D Kelas VII SMPN 3 Malinau Utara - Kuling Ngerung; Nerita Setianingtiyas (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2025)
This study aims to improve the learning outcomes of grade VII students at SMPN 3 North Malinau through the application of the Problem Based Learning (PBL) learning model in the subject of Catholic Religion. The background of this study is the low learning outcomes of students caused by lack of motivation, interest, and uninteresting learning methods. The application of PBL was chosen because it can improve critical thinking skills, collaboration, and problem solving that are relevant to everyday life. This study uses a classroom action research method with two cycles involving 8 students as research subjects. The results showed that the application of PBL significantly improved student learning outcomes, both in cognitive, affective, and psychomotor aspects. Therefore, the application of the PBL model is expected to improve the effectiveness of Catholic Religion learning at SMPN 3 North Malinau.